Knowledge Management-Based Efforts To Improve MSME Performance (Credit Union Intervention for MSME Actors in Sikka Regency) - Yustina Olivia Da Silva; Tobias Joni Temu; Paulus Libu Lamawitak (Dinasti Publisher, 2024)
This study aims to analyze the benefits of developing Knowledge Management strategies in an effort to improve the performance of MSMEs. Another aspect that receives attention in this paper is the role of credit cooperatives and the government as a catalyst for a joint movement to improve and strengthen the role of MSMEs in the regional economy. The method used is descriptive-qualitative with a literature study approach. The author tries to explore various sources related to the material of this writing. From the results of the literature study, it was found that the implementation of knowledge management needs support from credit cooperatives and local governments. The cooperative is a joint forum for MSME players to help each other in reducing various costs in the MSME business process. Meanwhile, the government is an important entity in ensuring the implementation of various government programs for the empowerment of cooperatives and MSMEs and ensuring that the implementation of various regulations relating to MSMEs is carried out carefully and on target.